Modifications to the Regime of Unsolicited Proposals in the Public Private Partnerships Law - Maraví Sumar, Milagros (2020)
The issue under investigation is limited to the experience of unsolicited proposals in Peru since 2003 with the implementation of the “Decentralized Investment Promotion Framework Law”, which deserves a review and analysis to propose improvements to this figure, through which relevant infrastructure projects, public services and investment in state assets have been developed. Therefore, the objective of this work is to establish the main problems related to unsolicited proposals such as the disincentive to private investment due to corruption issues; the existing problems related to the reimbursement of expenses incurred in the formulation and presentation of unsolicited proposals; the problems presented in the formulation of such initiatives; and finally, the legal nature of the admissibility of unsolicited proposals.